The Effectiveness of STEM-Based MURDER Learning Model Assisted by Quizizz to Improve Students' Numeration Ability - Jannah, Reni Roikhatul; Wardono, Wardono; Asih, Tri Sri Noor (Jurnal Pendidikan MIPA, 2023)
Abstract: The numeracy of 10th-grade students at SMAN 3 Slawi is still not optimal and needs improvement. This is because students are not accustomed to dealing with non-routine problems. This research aims to determine the effectiveness of the STEM-based MURDER learning model assisted by Quizizz in improving students' numeracy. In this study, the proportion test of student completeness obtained a Sig. value of 0.004, indicating that the proportion of students class experimental exceeded the classical completeness, reaching 42%. In the test of average differences, a Sig. value of 0.004 was obtained, meaning that the numeracy ability of the experimental group was higher than control group. In terms of improvement, the N-Gain test resulted 0.28, which falls into the interval 〈g〉 < 0.3, indicating that the improvement in students' numeracy using the STEM-based MURDER learning model assisted by Quizizz is relatively low. Keywords: numeracy, STEM, MURDER, quizizz. Abstrak: Numerasi siswa kelas X SMAN 3 Slawi masih belum optimal dan perlu ditingkatkan, hal tersebut terjadi karena siswa tidak terbiasa dengan permasalahan berupa soal non-rutin. Penelitian ini bertujuan untuk menentukan efektivitas model pembelajaran berbasis STEM MURDER yang dibantu oleh Quizizz dalam meningkatkan numerasi siswa. Dalam penelitian ini, uji proporsi ketuntasan siswa diperoleh nilai Sig. 0,004 dengan demikian proporsi ketuntasan siswa yang dikenai pembelajaran MURDER berbasis STEM berbantuan Quizizz melampaui tuntas secara klasikal mencapai 42%. Pada uji perbedaan rata-rata diperoleh nilai Sig. 0,004 yang artinya kemampuan numerasi siswa kelas eksperimen lebih dari numerasi siswa kelas kontrol. Dalam peningkatannya dilakukan dengan uji N-Gain diperoleh N-Gain score sebesar 0,28 berada pada interval 〈g〉 < 0.3, bahwa peningkatan numerasi siswa dengan menggunakan model pembelajaran MURDER berbasis STEM berbantuan Quizizz tergolong rendah.  Kata kunci: numerasi; MURDER; STEM; dan quizizz. DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp922-931